Перспективи виробництва харчових продуктів з використанням олійної та круп’яної сировини способом екструдування - Калина, Вікторія Сергіївна; Троєкурова, Віта; Луценко, Марина Василівна; Волосенков, Ігор; Kalyna, Viktoriia; Troiekurova, Vita; Lutsenko, Maryna; Volosenkov, Ihor (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто перспективи виробництва харчових продуктів із використанням олійної та круп’яної сировини способом екструдування як інноваційного напряму підвищення харчової й біологічної цінності продукту. Проаналізовано нутрієнтний склад насіння амаранту, кунжуту, арахісу, розторопші та сої. Узагальнено дані щодо харчової цінності круп’яної продукції. Установлено, що екструзійна технологія забезпечує інтенсифікацію технологічних процесів, модифікацію фізико-механічних і біохімічних властивостей готового продукту, що в комплексі сприяє зростанню його засвоюваності й енергетичної цінності. Запропоновано підходи до створення крохмально-олійних екструдованих продуктів. Перспективним напрямом є міждисциплінарна співпраця технологів, кулінарів і медичних фахівців щодо розробки рецептур круп’яних сумішей із додаванням олійних культур харчового призначення. Це створює передумови для розробки й виробництва нових круп’яних виробів оздоровчого та профілактичного призначення. /// EN: The article examines the prospects for the production of food products using oilseed and cereal raw materials by means of extrusion as an innovative approach to enhancing the nutritional and biological value of products. The nutrient composition of amaranth, sesame, peanut, milk thistle, and soybean seeds is analyzed; these raw materials are characterized by a high content of complete proteins, polyunsaturated fatty acids, dietary fiber, B vitamins, tocopherols, minerals, and biologically active compounds with antioxidant properties. The nutritional value of cereal products (oat flakes, buckwheat, rice, millet, pearl barley, barley groats, peas, and semolina) is also summarized, as they serve as important sources of complex carbohydrates, plant protein, fiber, and micronutrients. The feasibility of combining oilseed and cereal raw materials in extruded blends to develop products with targeted functional properties is substantiated. It is demonstrated that extrusion technology ensures process intensification and rapid modification of the physical-mechanical and biochemical characteristics of raw materials, increases the degree of starch gelatinization, promotes protein denaturation, and inactivates anti-nutritional factors, thereby improving digestibility and enhancing the energy value of the final product. It is concluded that the application of extrusion in cereal product manufacturing is both technologically and economically justified. A promising direction is interdisciplinary collaboration among food technologists, culinary specialists, and medical professionals to develop cereal blends enriched with edible oilseed crops. This approach creates the preconditions for the production of health-oriented cereal products, including those intended for preventive nutrition.
Prospects for the production of food products using oilseed and cereal raw materials by extrusion technology
Keywords: олійно-круп’яна інгредієнтна суміш; екструзійна технологія; крохмально-олійні екструдовані продукти; oil-and-cereal ingredient mixture; extrusion technology; starch-oil extruded products